Carreras académicas de mujeres en la Universidad de Costa Rica: Un reto para la igualdad - Mesa Peluffo, Sylvia (Universidad de Costa Rica, 2019)
This paper shares findings from a study conducted at UCR between 2016 and 2017. The research problem focused in factors influencing the academic careers of women turning them slower than men’s and thus they stay in lower positions compared them. Previous research points out disadvantages of women compared to men in teaching positions. Feminist qualitative methodology was used. Fourteen in depth interviews, with female teachers with more than 10 years’ experience, working in different areas in the UCR, were conducted. Analysis categories used were the following: Teaching experience and academic regime category; Maternity and teaching; Caring of children and other persons, Negotiation between family and academic activities; Influence of the above factors in their careers; Extended maternal roles; Difference in advance with male coworkers; The way sexism and discrimination influence both the academia and the way society considers women. Results: 1.Only four of these women are professors 2. The fact of being almost exclusively responsible for their children and caring of others, as well as extended maternal roles, hinder women's academic career. 3. Most of them have failed to negotiate the importance of their careers with their family. Conclusions: 1. Caring consumes time, thus physical and psychological space. 2. Sexism and discrimination are reflected both in the way women are treated, and in university norms. 3. Academic Regime regulations are not sensitive to gender.